Розробка, впровадження та автоматизація процесу бюджетування на підприємстві - Михайленко, Ольга Валеріївна; Свірідкіна, Ксенія Віталіївна (My University, 2019)
У статті викладено матеріал щодо формування механізму розроблення та впровадження автоматизованої системи бюджетування на підприємстві. Розглянуто основні теоретичні відомості щодо використання системи бюджетування та етапи впровадження автоматизованої системи бюджетування за центрами відповідальності. Для впровадження системи бюджетування на підприємстві використовуються як спеціалізоване програмне забезпечення, так й універсальні програмні рішення. Вибір програмного забезпечення залежить від можливостей та потреб компанії, її обсягів діяльності. Ґрунтовне впровадження системи бюджетування за розпорядниками бюджетів забезпечує підвищення ефективності діяльності компанії та дає змогу на основі отриманої інформації планувати майбутні витрати як в короткостроковій, так і в довгостроковій перспективі. The article describes the formation of a mechanism for the development and implementation of an automated budgeting system at the enterprise. The main theoretical information regarding the use of the budgeting system and the stages of implementation of the automated budgeting system by the cen¬ters of responsibility are considered. Due to changes over the past decades in the socio-economic envi¬ronment have created conditions for the emergence of market management methods. Due to this the introduction of methods of effective enterprise management, their constant improvement at all stages of the enterprise, such as supply, production, storage, organization of business processes and others. One of the main factors of such actions is to improve the activity of enterprises, to minimize costs and maximize profits. To ensure the best results of the company, the theoretical and methodological prin¬ciples of management accounting, analysis of the results and decision making based on the performed actions are used. Budgeting as a process is consistent with the design, implementation, control and analysis of the budget, with subsequent possible adjustments to both the plans and objectives of the enterprise. Budgeting, accounting, monitoring, and analyzing “budgeting responsibility centers” are a system that measures (evaluates) plans and actions for each center of responsibility. The mecha¬nism of accountability accounting is an integral and obligatory component of the business budgeting at all three stages (compilation of the consolidated budget, control over implementation, and plan-fact analysis of implementation). Without stiffening the responsibility, the approved consolidated budget project will remain no more than a “good intentions”. To implement the budgeting system, specialized software and universal software solutions are used at the enterprise. The choice of software depends on the company’s capabilities and needs, its scope of activities. The thorough implementation of the budgeting system by the budget administrators ensures an increase in the efficiency of the company’s area and allows, based on the information received, to plan future costs, both in the short and long term
Keywords: бюджет; бюджетування; автоматизація бухгалтерського обліку; центри відповідальності; програмне рішення; budget; budgeting; automation of budgeting system; centers of responsibility; software solution; кафедра обліку і аудиту